Influence of the Seagrass, Zostera marina, on Wave Attenuation and Bed Shear Stress Within a Shallow Coastal Bay - Reidenbach, Matthew A.; Thomas, Emily L. (Frontiers in Marine Science, 2018)
Local effects of flow interaction with seagrass structure modify meadow scale hydrodynamics, resulting in lower current velocities and wave heights within a seagrass meadow. This attenuation promotes the deposition of suspended sediment, increasing the light available locally to benthic organisms. To elucidate the relationship between small-scale hydrodynamics that occur at the sea floor and the meadow scale effects of seagrass, high resolution velocity profiles were recorded adjacent to the sediment-water interface within a Zostera marina seagrass meadow in South Bay, Virginia. Additionally, instrumentation was deployed across the meadow to seasonally monitor corresponding changes in wave height across the seagrass meadow. Results show that wave height was reduced by 25 – 49% compared to an adjacent bare site, and by 13 – 38% compared to an analytical model of wave attenuation over an unvegetated seafloor with the same bathymetry. The greatest attenuation of wave height occurred during the spring and summer when seagrass biomass was greatest, while the lowest attenuation occurred in winter, corresponding to periods of minimal seagrass biomass. Significant wave height attenuation coefficients, αw, calculated for the meadow ranged from αw = 0.49 in spring to 0.19 during winter, but were highly dependent on wave conditions, with greater αw for larger wave heights and longer period waves. Within the seagrass meadow during summer, the highest measured bed shear stress was t_bed = 0.034±0.022 Pa, which occurred during peak wave conditions. This suggests that during high biomass conditions, the bed shear stress rarely exceeds the critical bed shear, t_crit = 0.04 Pa necessary to initiate sediment resuspension. This is in contrast to the bare site which showed elevated values of t_bed above the critical threshold across all seasons. These findings suggest the seagrass meadow does exert significant control over both wave heights and the hydrodynamic conditions at the sediment-water interface, and this control is due to the attenuation of wave motion by drag induced from the seagrass over the expanse of the meadow.